2020
DOI: 10.1186/s12964-020-0516-2
|View full text |Cite
|
Sign up to set email alerts
|

Natural biased signaling of hydroxycarboxylic acid receptor 3 and G protein-coupled receptor 84

Abstract: Background: Medium-chain fatty acids and their 3-hydroxy derivatives are metabolites endogenously produced in humans, food-derived or originating from bacteria. They activate G protein-coupled receptors, including GPR84 and HCA 3 , which regulate metabolism and immune functions. Although both receptors are coupled to G i proteins, share at least one agonist and show overlapping tissue expression, GPR84 exerts pro-inflammatory effects whereas HCA 3 is involved in anti-inflammatory responses. Here, we analyzed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 59 publications
3
23
0
Order By: Relevance
“…In contrast to the more prevalent (R)-hydroxy fatty acids in mammals that we might generate or consume directly, (S)-3-hydroxy fatty acids, including (S)-3-hydroxy capric acid, are components of LPS in Gram-negative bacteria and used as endotoxin markers in clinical samples ( Jenske and Vetter, 2009). Peters et al (2020) hypothesize that GPR84 has a protective role against pathogenic bacteria based on the proinflammatory response to 3-hydroxy capric acid. The characterization of hydroxylated MCFA enantioselectivity has the potential to provide important clues to the function of GPR84 and is the subject of future work.…”
Section: Potential Nondietary Mcfa Metabolitesmentioning
confidence: 99%
“…In contrast to the more prevalent (R)-hydroxy fatty acids in mammals that we might generate or consume directly, (S)-3-hydroxy fatty acids, including (S)-3-hydroxy capric acid, are components of LPS in Gram-negative bacteria and used as endotoxin markers in clinical samples ( Jenske and Vetter, 2009). Peters et al (2020) hypothesize that GPR84 has a protective role against pathogenic bacteria based on the proinflammatory response to 3-hydroxy capric acid. The characterization of hydroxylated MCFA enantioselectivity has the potential to provide important clues to the function of GPR84 and is the subject of future work.…”
Section: Potential Nondietary Mcfa Metabolitesmentioning
confidence: 99%
“…3-hydroxydecanoic acid is a medium-chain fatty acid, whose sensing receptor GPR84 is a pro-inflammatory receptor [ 30 ]. Peters et al declared that 3-hydroxydecanoic acid can stimulate GPR84 and cause a sustained ERK activation [ 31 ]. The ERK pathway was closely related to the human immunodeficiency regulatory protein, which can enhance the replication and infectivity of viruses such as HIV by regulating T-cell activity [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…As it turned out, one of the possible explanations may be related to the activation of the hydroxycarboxylic acid receptor 3 (HCA3) by capric acid, which is included in the mixture used in our experiments. Peters A. et al found that the hydroxylated metabolite of this acid (3-OHC10) was able to activate not only GPR84 (with the same efficiency as the native C10), but also the HCA3 receptor [6]. Similar to the mediumchain fatty acid receptor, HCA3 is expressed on immune cells.…”
Section: Resultsmentioning
confidence: 99%